PENGARUH MODEL OPEN ENDED TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP - Noviyana, Hesti (JURNAL e-DuMath, 2018)
Abstract: The research problem is related to students mathematical problem solving ability and application of Open Ended model. The purpose of this research is to know the influence of Open Ended model on mathematical problem solving ability of grade VIII SMP students. Research using experimental method. Data analysis using parametric statistics. Research population of all students of grade VIII SMP Negeri 1 Candipuro Lampung Selatan, the sample is taken 2 classes, namely VIII A as experimental class and VIII C as a control class taken using Cluster Random Sampling technique. Mathematical problem solving ability is measured with essay test of 5 questions. Hypothesis testing uses t-test, with t value = 9,07. At significance level 5% known tdaf =Â 2.00 means thit > tdaf that is 9.07> 2.00, so it is concluded